IMPROVING ENERGY EFFICIENCY IN FOOD PRODUCTION - Sobirov, M.N. (Educational Research in Universal Sciences, 2023)
The article presents the importance and problems of food production. Proposals for increasing energy efficiency and reducing waste in food production have been developed. The advantages of using energy-efficient lighting methods in industrial enterprises are shown. The energy and technologies used for heating and cooling houses and industrial buildings were analyzed. Proposals have been developed to improve the efficiency of using energy-using devices in enterprises. Conclusions are given on the importance of minimizing food waste. The importance of qualified personnel in achieving energy efficiency in food production and the need to use creative methods of personnel training were emphasized. Conclusions are made on the importance of increasing equipment utilization efficiency by investing in energy-efficient equipment and implementing automation systems, and minimizing food waste through proper storage practices and optimizing inventory management.